Secondary School Teachers’ Participation in Decision Making Process in Eastern Province, Kenya - Mulwa, David Musyoki (International Journal of Education and Research, 2015)
The purpose of the study was to investigate the teachers’ participation in decision making process in secondary schools of Eastern Province, Kenya. The objectives of the study were to identify the key decision makers in selected management tasks in public secondary schools as perceived by teachers and to find out the adequacy of their involvement in decision making. It was also aimed at establishing if there is a difference between the teachers’ perception on the adequacy of their involvement in decision in decision process and the gender and the teaching experience of the teachers, and the type of school. Data was collected by the use of a questionnaire. Data was analyzed by the use of descriptive and inferential statistics. The findings of the study were that the key decision makers in curriculum and instruction programme were the principals and teachers while in students’ management and welfare, the key decision makers were the principals, teachers and Boards of governors. In school finance management, the key decision makers were identified as the Principals and Boards of Governors. It was also found out that there was an association between the teaching experience of teachers and their perception on the adequacy of their involvement in decision making process in secondary schools of Eastern Province, Kenya.
Keywords: Decision Making; Participation; Management Tasks